2010
DOI: 10.1371/journal.pone.0015212
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Muscle Satellite Cell Activation and Chemotaxis by Angiotensin II

Abstract: The role of angiotensin II (Ang II) in skeletal muscle is poorly understood. We report that pharmacological inhibition of Ang II signaling or ablation of the AT1a receptor significantly impaired skeletal muscle growth following myotrauma, in vivo, likely due to impaired satellite cell activation and chemotaxis. In vitro experiments demonstrated that Ang II treatment activated quiescent myoblasts as evidenced by the upregulation of myogenic regulatory factors, increased number of β-gal+, Myf5-LacZ myoblasts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
2
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 46 publications
1
31
2
1
Order By: Relevance
“…We also found that differentiated satel-lite cells expressed the AT2R. Our findings were consistent with reports that AT1R blockade or AT1R deficiency was beneficial in mouse models of myopathy and injury (21,22), although there are contradictory reports that an angiotensinconverting enzyme inhibitor or AT1R ablation significantly impaired skeletal muscle regeneration (23,24).…”
supporting
confidence: 91%
“…We also found that differentiated satel-lite cells expressed the AT2R. Our findings were consistent with reports that AT1R blockade or AT1R deficiency was beneficial in mouse models of myopathy and injury (21,22), although there are contradictory reports that an angiotensinconverting enzyme inhibitor or AT1R ablation significantly impaired skeletal muscle regeneration (23,24).…”
supporting
confidence: 91%
“…1, F and G, and 4A). Johnston et al (36) reported that Ang II increased Myf5, MyoD, Pax7, cyclin D1, and AT1R mRNA levels in C2C12 cells but that these cells express very low levels of Ang II receptors (22), and the dose of Ang II used in this study (10 M) was supraphysiological (39). In our experimental setting, 100 nM Ang II was sufficient to reduce MyoD and myogenin expression, Notch activation, and satellite cell proliferation in vitro (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Previous reports indicate that angiotensin-converting enzyme inhibitors impaired skeletal muscle growth following CTX-induced injury (36) and attenuated overload-induced skeletal muscle hypertrophy (37,38), suggesting that Ang II may be a positive regulator of muscle growth and regeneration. However, our data clearly show that Ang II prevents muscle regeneration as early as 3 days after injury, at which time there is reduced expression of MyoD and myogenin and attenuation of Notch activation (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…This group includes ACE (angiotensin-converting enzyme), Bdkrb1 (bradykinin receptor, b1), RGS2/5 (regulator of G-protein signalling 2 and 5) and Gem (GTP binding protein; gene overexpressed in skeletal muscle) (supplementary material Table S2). These genes can be linked to the angiotensin pathway which has recently been associated with satellite cell function (Johnston et al, 2010). Recently it has been demonstrated that the Hippo pathway is regulated G-proteincoupled receptor signalling (Yu et al, 2012) and it is intriguing that high Yap activity transcriptionally inhibits several members of this pathway in myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Like NDRG2, Myf6 (Mrf4) is repressed by hYAP1 S127A overexpression. Myf6 is a myogenic determination gene (Kassar-Duchossoy et al, 2004) whose expression increases, unlike that of MyoD and Myf5, late during myogenic differentiation (Tomczak et al, 2004). This involves an involvement in terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%